Justification of the Forming Mechanism of a Supply Chains by Regional Tourist Cluster Competitiveness - A. Nigay, Evgeniya; Lebedinskaya, Yulia S. (International Journal of Supply Chain Management, 2019)
The competitiveness of the region and prosperity of economy are substantially caused by forming of competitive industry clusters in the supply chain strategy. With a force of the industry clusters making it the extensive list of scientific works is devoted to questions of a research of interrelation of competitive positions of the region. However today there is no standard approach to selection of indicators of competitiveness of a tourist cluster and to its assessment. Authors present an integrated approach to assessment of competitiveness of a tourist cluster of the region on the basis of a rhombus of competitive advantages of M. Porter and the system of accumulation of cost by subjects of this education in article. According to the offered approach the competitiveness of a tourist cluster of the region forms proceeding from complex assessment of competitiveness of every one of subjects in its structure. At the same time the competitiveness of subjects of a tourist cluster is measured proceeding from the competitive advantages reached by it. The combination of competitive advantages, participants of a cluster as well as their interaction provide synergy effect in improving competitiveness of a tourist cluster and, as a result, the region.